2022
DOI: 10.1590/1980-5373-mr-2021-0602
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Mechanical Properties and Strain-induced Crystallisation of Epoxidized Natural Rubber Filled with Various Silanized Halloysite Nanotubes

Abstract: Natural rubber (NR) and halloysite nanotube (HNT) composites are known to perform poorly due to polarity differences between the two components. As such, many extant studies have attempted to increase their compatibility. Therefore, this study introduced epoxidized natural rubber (ENR) together with silane coupling agents into the composite to ensure rubber-filler interactions. Four different silanes namely bis-[(triethoxysilyl)propyl] disulphide (TESPD), bis[(triethoxysilyl)propyl] tetrasulfide (TESPT), triet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The specimens with biochar showed a decrease in tensile strength of about 3.0, 56.9 and 53.8% for the NR/BIO30min, NR/BIO60min and NR/BIO240min compounds respectively when compared to the unfilled specimen reinforcement (NR). This decrease in tensile strength is due to the change in the extension of the stretch crystallization process of natural rubber, 43 as the crystalline properties of the biochar, which change with increasing residence time in the reactor, reduce the flexibility of the chains. The higher the crystallinity (longer residence time) of the biochar, the lower is the tensile strength.…”
Section: X-ray Diffraction Analysis Of Biochar Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…The specimens with biochar showed a decrease in tensile strength of about 3.0, 56.9 and 53.8% for the NR/BIO30min, NR/BIO60min and NR/BIO240min compounds respectively when compared to the unfilled specimen reinforcement (NR). This decrease in tensile strength is due to the change in the extension of the stretch crystallization process of natural rubber, 43 as the crystalline properties of the biochar, which change with increasing residence time in the reactor, reduce the flexibility of the chains. The higher the crystallinity (longer residence time) of the biochar, the lower is the tensile strength.…”
Section: X-ray Diffraction Analysis Of Biochar Samplesmentioning
confidence: 99%
“…The higher the crystallinity (longer residence time) of the biochar, the lower is the tensile strength. 43 Fillers with different properties, such as crystal structure and texture, affect the interaction with the rubber by modifying crystallization through stretching; usually the addition of fillers slows down this process. 43 For fillers with high structure, such as carbon black and BIO30min, which have a turbostratic structure, the crystallites tend to have the same size, making the tensile strength close to these compounds, provided that the particle size is the same.…”
Section: X-ray Diffraction Analysis Of Biochar Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the methods has been the addition of a compatibilizer or coupling agent. There have been many types of compatibilizers and/or coupling agents used for NR/HNT composites [ 13 , 14 , 15 ]. Over the years, silane coupling agents have been extensively used and studied.…”
Section: Introductionmentioning
confidence: 99%
“…Many types of silane have been grafted onto HNT when preparing polymer composites. Masa and Hayeemasae [ 14 ] used various types of silane in the ENR/HNT composites. It was reported that sulfur-based silane had given optimum properties.…”
Section: Introductionmentioning
confidence: 99%